Tinjauan Engagement dan Perolehan Komisi Host Talent Live Streaming Tiktok - Dayu Novi Andari; Hamzah Robbani; Alin Alianny (FOCUS, 2023)
This research aims to conduct an in-depth review of the phenomenon of engagement and earning commissions from Live Streaming TikTok talent hosts with the @dayu.na case study. The research approach used is quantitative with a causal descriptive design. The population that is the focus of the research is all TikTok users who have an account and access the Live Streaming feature, while the sample taken is host talent @dayu.na, who is actively doing Live Streaming in the period August-November 2022. The data in this study were collected through two techniques. . First, direct observation was made on Live Streaming @dayu.na to record the number of viewers, likes, comments, and virtual gifts given by the audience during the broadcast. Second, secondary data is obtained from TikTok Analytics, which includes data on commissions earned from the virtual gift feature, and other statistical data available from the TikTok application. The results of the data analysis show that there is a positive relationship between a high level of engagement and significant commission earnings. In other words, the higher the engagement obtained from the audience during Live Streaming, the greater the commission received by the host talent @dayu.na. This research provides a deeper understanding of the business potential of Live Streaming on the TikTok platform. The findings of this research can provide relevant insights for content creators and users of other social media platforms in utilizing engagement to increase revenue through Live Streaming. The implications of this research can also contribute to the development of social media as an effective business tool in this modern era.